2019
DOI: 10.7189/jogh.09.020432
|View full text |Cite
|
Sign up to set email alerts
|

Ability of shock index and heart rate to predict the percentage of body blood volume lost after vaginal delivery as an indicator of severity: results from a prospective cohort study

Abstract: BackgroundPostpartum hemorrhage (PPH) is the leading cause of maternal mortality worldwide, but it mainly affects women from low- and middle-income countries. Despite being a treatable condition, the high number of maternal deaths resulting from PPH is outstanding for at least 25 years. Late diagnosis and difficulties in identifying women who will develop severe postpartum bleeding can, in part, explain the high incidence of PPH. Over the past few years, researchers have focused on identifying a simple, access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Borovac-Pinheiro et al reported the amount of postpartum bleeding and vital signs in normal pregnancy over 24 h. Seventy-three percent of the amount of 24 h bleeding was lost in the first 40 min after delivery, and 91% of participants had 90% of the amount of 24 h bleeding within 2 h after delivery. 3 It is considered that the evaluation of the amount of bleeding up to 2 h after delivery is a valid evaluation method in our study examining the management of postpartum blood loss.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Borovac-Pinheiro et al reported the amount of postpartum bleeding and vital signs in normal pregnancy over 24 h. Seventy-three percent of the amount of 24 h bleeding was lost in the first 40 min after delivery, and 91% of participants had 90% of the amount of 24 h bleeding within 2 h after delivery. 3 It is considered that the evaluation of the amount of bleeding up to 2 h after delivery is a valid evaluation method in our study examining the management of postpartum blood loss.…”
Section: Discussionmentioning
confidence: 98%
“…2 SI and HR are utility index in predicting postpartum hemorrhage (PPH) in pregnant women without complications such as hypertension. 3 PPH is defined as greater than 500 ml estimated blood loss in delivery. However, there are few reports of SI in pregnant women complicated with hypertensive disorders in pregnancy (HDP) cases.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the amount of blood loss occurs within two hours after delivery. 23 Borovac-Pinheiro et al stated that PPH treatment should be started as suspected to prevent excessive blood loss. This initiation should be within the first hour of delivery, preferably within 30 minutes of delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, opioids are less effective than dexmedetomidine in reducing HR. Decreased mean arterial pressure without controlled HR does not lead to improved visibility or lessened bleeding [ 22 , 23 ]. In addition, the vasoconstrictive effect of intravenous dexmedetomidine has been demonstrated in animal models [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%